Reuse of Waste Foundry Sand Mixed with Lateritic Clayey Soils in Pavement Bases and Sub-bases Courses - Gutierrez Klinsky, Luis Miguel; Pessa Fabbri, Glauco Tulio; Santos Bardini, Vivian Silveira dos [UNESP]; Canestrari, F.; Partl, M. N. (Springer, 2016)
This paper evaluated the reuse of WFS mixed with lateritic clayey soils in pavements sub-bases and bases. Two lateritic clayey soils and one chemically bonded WFS were used in this study. A laboratory program was conducted on mixtures of lateritic clayey soils and WFS. Atterberg Limits, Particle Size Distribution, mini-CBR, CBR, hydraulic conductivity and Cyclic Triaxial Tests were used to assess mechanical properties of soil-sand mixtures. Environmental test was performed to determine leaching potential of the WFS. The results showed that soil-sand mixtures containing WFS have mechanical properties similar to the materials commonly used in bases and sub-bases courses.
Keywords: Waste foundry sand; Soil stabilization; Base and Sub-base courses; CBR; Resilient modulus